Socio-Cultural Impacts of COVID-19 in Nepal - Gyanwali, Gokarma Prasad (Molung Educational Frontier, 2020)
The COVID-19 pandemic has considerably distorted the social and cultural life of people on a global scale. It has a profound impact on the dynamics of human mobility, in & out - migration, economy, and socio-cultural correlation that underpin population diversity. It seen that some of these effects are short-lived, but others will have long-lasting implications that can see in the future. The COVID-19 crisis is exposing the fragility of all our systems, our complex dependence upon one another, livelihood patterns and health, and healthcare as the most basic of human rights. Health security is one of the essential parts of social safety, which encompasses material or economic security; the security of life, and protection from violence and conflict, and these all are apprehensive and questionable in this pandemic. Like other developed and developing countries, Nepal is also facing the challenges contrived by the pandemic. This article describes the impacts of COVID-19 in socio-culture sectors and the diverse categories of the people of Nepal.